Modern democracy as a divinization of man in Nicolás Gómez Dávila. (2021)
As a result of a research on political philosophy and political theology, this article explores the idea of Colombian thinker Nicolás Gómez Dávila according to which all politics implies theology and, specifically, modern democracy consists, fundamentally, in the divinization of a man who proclaims himself sovereign in the metaphysical, ethical, political and legal fields. Based on the interpretation of the work by Gómez Davila and the dialogue with authors specialized in political and legal theology, such as Alvear, Guardini, Jonas, Schmitt, and Voegelin, the main arguments of his theological understanding of modern democracy will be studied from the concept of religious analysis. First, this paper will present a brief biographical sketch of Gómez Dávila. Afterwards, it will explain the relation that, according to Gómez, exists between gnosis and the Enlightenment. A third moment will address the idea of democracy as an anthropotheistic creed. Finally, the main conclusions resulting from this research will be presented.